MODEL DAN PENGUKURAN NILAI TUKAR NELAYAN (KASUS KABUPATEN KARANGASEM) - USTRIYANA, I NYOMAN GEDE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 7, No. 1 February 2007)
ABSTRACT The paper discusses how to do design and measure Terms of Trade of Fisherman (Nilai Tukar Nelayan). The research is a part of join research between Department of Socio- Economics Agriculture Udayana University and Bali Provincial Government of Fisheries and Maritime. The research used Terms of Trade of Fisherman soft-ware designed by the Ministry of Maritime and Fisheries. The result of the study found that the value of Term of Trade of Fisherman is just below one. Key Words: Terms of Trade, Fisherman ABSTRAK Tulisan ini mendiskusikan tentang model dan pengukuran Nilai Tukar Nelayan (NTN), yang merupakan hasil penelitian kerjasama antara Jurusan Sosial Ekonomi Pertanian Universitas Udayana dengan Dinas Perikanan dan Kelautan Provinsi Bali. Penelitian menggunakan software dari Departemen Kelautan dan Perikanan. Hasil penelitian memperlihatkan bahwa NTN di Kabupaten Karangasem berada dibawah satu. Kata kunci: Nilai Tukar Nelayan, Nelayan
Keywords: Terms of Trade, Fisherman (Nilai Tukar Nelayan, Nelayan)